Bleb expansion requires transient membrane invaginations that sequester curvature-preferring proteins - Yuki Maekawa; Saori R. Yoshii; Noboru Mizushima; Junichi Ikenouchi (Proceedings of the National Academy of Sciences, 2026)
Bleb-based cell migration involves rapid plasma membrane expansion driven by intracellular pressure. How the membrane reorganizes its curvature and protein composition during this process remains unclear. Here, we identify a distinct inward membrane structure, termed the sub-bleb invagination (SBI), that forms de novo at the bleb base during expansion. SBIs display strong positive curvature and transiently sequester curvature-preferring integral membrane proteins such as Caveolin-1 and Piezo1 without endocytosis. Live-cell imaging shows that these proteins transiently accumulate at the SBIs in concert with bleb growth, indicating that bleb expansion dynamically redistributes membrane curvature and protein localization. Overexpression of curvature-preferring proteins markedly inhibited bleb enlargement and induced the aberrant formation of SBI-like membrane invaginations, suggesting that their excessive accumulation limits the membrane from unfurling. Our findings reveal a curvature-based mechanism for membrane protein sorting during bleb expansion and highlight how the interplay between membrane curvature and integral membrane protein organization shapes PM dynamics.